A developmental sensitive period for spike timing-dependent plasticity in the retinotectal projection - Tsui, Jennifer; Schwartz, Neil; Ruthazer, Edward S. (Frontiers in Synaptic Neuroscience, 2010)
The retinotectal projection in Xenopus laevis has been shown to exhibit correlation-based refinement of both anatomical and functional connectivity during development. Spike timing-dependent plasticity (STDP) is an appealing experimental model for correlation-based synaptic plasticity because, in contrast to plasticity induction paradigms using tetanic stimulation or sustained postsynaptic depolarization, its induction protocol more closely resembles natural physiological activity. In Xenopus tadpoles, where anatomical remodeling has been reported throughout much of the life of the animal, in vivo retinotectal STDP has only been examined under a limited set of experimental conditions. Using perforated patch recordings of retina-evoked EPSCs in tectal neurons, we confirmed that repeatedly driving a retinotectal EPSP 5-10 ms prior to inducing an action potential in the postsynaptic cell, reliably produced timing-dependent long-term potentiation (t-LTP) of the retinotectal synapse in young wild type tadpoles (stages 41-44). At these stages, retinotectal timing-dependent long-term depression (t-LTD) also could be induced by evoking an EPSP to arrive 5-10 ms after an action potential in the tectal cell. However, retinotectal STDP using this standard protocol was limited to a developmental sensitive period, as we were unable to induce t-LTP or t-LTD after stage 44. Surprisingly, this STDP protocol also failed to induce reliable STDP in albino tadpoles at the early ages when it was effective in wild type pigmented animals. Nonetheless, low-frequency flashes to the eye produced a robust NMDA receptor-dependent retinotectal LTD in stage 47 albino tadpoles, demonstrating that the retinotectal synapse can nonetheless be modified in these animals using different plasticity paradigms.